Interindividual variability of internal transcribed spacer region of ribosomal DNA in Rotylenchulus reniformis - Deng Yanfeng; Xu Hongbing; Tian Zhongling; Zheng Jingwu (浙江大学学报. 农业与生命科学版)
Ribosomal RNA gene (rDNA) is conservative and it is composed of numerous copies of tandemly repeated transcription units within the genome that has been recognized as an attractive marker for phylogenetic studies. It consists of the 18S, 5.8S, and 28S genes as well as internal transcribed spacer (ITS) region and external transcribed spacer (ETS) region. As members of a sequence family, the multiple copies of the rDNA do not evolve independently. They tend to evolve in a concerted fashion, which means that in a species the repeats evolve together. Previous study shows that there are two major variants in the 18S rRNA gene of the single Rotylenchulus reniformis.The variation within ITS region of rRNA gene among R. reniformis populations from Zhejiang, Fujian and Chongqing of China was reported. Two bands of 18S-ITS sequence with lengths of 1 250 bp and 1 400 bp (include ≈480 bp 18S rDNA sequence, the whole ITS sequence and ≈50 bp 28S rDNA sequence) were amplified from each nematode of three populations of R. reniformis, which named as variant 1 (RN_VAR1) and variant 2 (RN_VAR2), respectively. The amount of variation was assessed by sequencing five clones from each variant from six female reniform nematodes of three populations, with a total of 60 sequences. These sequences were distinguished, based on multiple sequence alignment (MSN), the percent identity and guanine and cytosine content (GC) content of the ITS and clustering in phylogenetic trees. The length and GC content of ITS region were characterized by RN_VAR1 (705-712 bp, 45.1%-46.7%) and RN_VAR2 (854 860 bp, 48.4%-50.0%), respectively. The percent identity between RN_VAR1 and RN_VAR2 was relatively low which only ranged between 62.1% and 65.6%. The percent identity between all clones in RN _ VAR1 was 89.9%-100%, and that in RN_VAR2 was 91.4%-99.8%. Phylogenetic tree analyses based on neighbor-joining method showed that both RN variants could be distinguished from other nematodes by ITS sequence alignment, while it was hard for differentiation of R. reniformis intrapopulation. The quantitative real-time polymerase chain reaction (qPCR) experiments showed that RN_VAR1 made up 56% of rDNA units with relatively well-conserves in 18S RNA gene, whereas RN_VAR2 was 40%. The two ITS variants, RN_VAR1 and RN_VAR2, were consistent to the reported two 18S RNA gene variants, respectively.The results confirm that there are two rDNA variant types in reniform nematode. This variation may be as a result of ancestral interspecific hybridization or gene recombination between sister chromatids, leading to the coevolution of the rDNA sequences on these chromosomes.